2020
DOI: 10.21608/svuijas.2020.27347.1008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of foliar application with seaweed extract, amino acids and vitamins on yield and berry quality of some Grapevine cultivars

Abstract: Experiments were conducted during four consecutive seasons of 2017, 2018, 2019 and 2020 on three grape cultivars including "Bez-El-Anza", "Thompson Seedless" and "Red Roomy" planted at the Experimental Orchard of fruit section, Faculty of Agriculture, Assiut University in a complete randomized blocked design. This investigation was carried out to study the effect of spraying Seaweed extract, Amino acids and Vitamins on C/N ratio, yield and berry quality of some grape cultivars. The obtained results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The positive effect of amino acid on improving pruning wood weight, ripening wood, internode length and thickness could be attributed to its major role on stimulating cell division and elongation, carbohydrate assimilation, photosynthesis, nucleic acid and protein synthesis (El-Sese et al, 2020) and this reflected on improving vegetative growth, physiological status and subsequently, reflected on improving the previous properties.…”
Section: Parameters At Dormant Seasonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive effect of amino acid on improving pruning wood weight, ripening wood, internode length and thickness could be attributed to its major role on stimulating cell division and elongation, carbohydrate assimilation, photosynthesis, nucleic acid and protein synthesis (El-Sese et al, 2020) and this reflected on improving vegetative growth, physiological status and subsequently, reflected on improving the previous properties.…”
Section: Parameters At Dormant Seasonsmentioning
confidence: 99%
“…El-Sherbeny and Da silva (2013) found that using tyrosine improve to be successful agents in enhancing vegetative growth and production quality of beet plants, Beet root producers can effectively use these tyrosine to improve crop for edible purposes and to improvement pigments for extraction for use in colouration and medicinal industries. El-Sese et al (2020) showed that tyrosine at 500 ppm recorded the highest yield of Red Roumy grapevine.…”
Section: Introductionmentioning
confidence: 99%
“…Hass and Shepard [101]. It was reported by many authors that spraying SWE was more effective in enhancing vegetative growth, yield, fruit chemical and physical characteristics and the nutritional status of grapes when compared to untreated trees [102][103][104]. In previous studies, it was found that treating orange trees with SWE led to an increase in the maturity index and yield, while simultaneously reducing fruit drop [105,106].…”
Section: Discussionmentioning
confidence: 99%